Motivational Factors and Obstacles to Entrepreneurial Intention Among Business Students - Ku Naraini, Che Ku Yusof; Izah, Mohd Tahir; Rosmaria, Jaffar @ Harun; Mohd Jaffri, Abu Bakar (2014)
Entrepreneurship education is considered important and is integrated in the curriculum of undergraduate studies in the higher institutions in Malaysia. However, not all students have the intentions to become entrepreneur once they graduated from the university. This paper investigates the motivational factors and the obstacles among business students in their intention to become entrepreneur. Structured questionnaires adopted from previous studies were distributed to 294 business students doing their undergraduate studies in one of the public university in Malaysia. The results found that the main motivational factors are to realize their dream, maintain their family and opportunities available in the market. The students perceived that the main obstacles faced are lack of savings, lack of business experience, uncertainty of future if they start business and fail to build trust among partners. These findings could be used to assist students in their future career to become an entrepreneur.